2016
DOI: 10.1016/j.scitotenv.2015.08.142
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends for inflow of perfluorooctanesulfonate (PFOS) and perfluorooctanoate (PFOA) to Tokyo Bay, Japan, estimated by a receptor-oriented approach

Abstract: We estimated inflow rates of perfluorooctanesulfonate (PFOS) and perfluorooctanoate (PFOA) to Tokyo Bay, Japan, between February 2004 and February 2011 by a receptor-oriented approach based on quarterly samplings of the bay water. Temporal trends in these inflow rates are an important basis for evaluating changes in PFOS and PFOA emissions in the Tokyo Bay catchment basin. A mixing model estimated the average concentrations of these compounds in the freshwater inflow to the bay, which were then multiplied by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 43 publications
0
10
1
Order By: Relevance
“…PFOS showed statistically significant declining trends in several surface waters, namely; in Tokyo Bay between 2004 and 2006 [129], in marine and fresh waters on the west coast of South Korea between 2008 and 2012 [95] and in Bohai Bay on the east coast of China between 2011 and 2013 [140]. The other significant downward trends for PFOS were observed in a digested sewage sludge sampled in Hinwil in Switzerland between 1998 and 2008 [136], in a Snow core from the Devon ice cap [91] and in a sediment core in the Haihe River (core S6, dated 1952-2006) in China [149].…”
Section: Abiotic Samplesmentioning
confidence: 97%
See 1 more Smart Citation
“…PFOS showed statistically significant declining trends in several surface waters, namely; in Tokyo Bay between 2004 and 2006 [129], in marine and fresh waters on the west coast of South Korea between 2008 and 2012 [95] and in Bohai Bay on the east coast of China between 2011 and 2013 [140]. The other significant downward trends for PFOS were observed in a digested sewage sludge sampled in Hinwil in Switzerland between 1998 and 2008 [136], in a Snow core from the Devon ice cap [91] and in a sediment core in the Haihe River (core S6, dated 1952-2006) in China [149].…”
Section: Abiotic Samplesmentioning
confidence: 97%
“…PFOA showed statistically significant declining trends in the same surface waters for which declining PFOS trends were also observed, namely; in Tokyo Bay between 2004 and 2006 [129], in marine and fresh waters on the west coast of Korea between 2008 and 2012 [95] and in Bohai Bay on the east coast of China between 2011 and 2013 [140]. Other data sets provided less than 7 time points and were not analysed for change-points.…”
Section: Pfoa (C8 Pfca)mentioning
confidence: 99%
“…Previous published scientific studies reported that PFOS exists widely in rivers, lakes and oceans (Yamashita et al, 2005;Munoz et al, 2015;Sakurai et al, 2016). Considering Yellow-Bohai Sea as a case area, the maximal concentration in sea water of PFOS was reported to be about 30.9 ng L À1 in coastal areas of Bohai Sea (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…33 Tokyo Bay is a large semienclosed marine environment with a surface area of approximately 992 km 2 and a mean depth of approximately 15-19 m. 34,35 It receives wastewater from a catchment inhabited by approximately 29 million people. 36 Approximately 8.7 million of these people live in Tokyo itself and the rest live in the surrounding area draining to the Bay. It is assumed that the entire population is served by good wastewater treatment.…”
Section: Methodsmentioning
confidence: 99%
“…It is assumed that the entire population is served by good wastewater treatment. 33,36 It is also assumed that there is no degradation or volatilisation of cVMS compounds discharged to rivers before these rivers reach the Bay (although we recognise that, in reality, there are likely to be losses of cVMS compounds from some discharge points where rivers are distant from the Bay). The dimensions and properties for Tokyo Bay adopted in the QWASI modelling described here are shown in Table S2.…”
Section: Methodsmentioning
confidence: 99%